Augmented Reality Books: Motivation, Attitudes, and Behaviors of Young Readers - Roumba, Evanthia; Nicolaidou, Iolie (International Journal of Interactive Mobile Technologies (iJIM), 2022)
Augmented Reality (AR) books show potential to increase young learners’ reading motivation, which is important given children’s declining reading motivation over the school years. Previous studies measured reading motivation only in higher education and only after users’ experience with AR. Few empirical studies have focused on school-aged children and those examined attitudes, not motivation. This study aimed to: a) examine how young children’s motivation changes through the experience of reading AR books and b) document their attitudes and behaviors after this experience. Participants in this pre-test post-test case study were 40 fourth and fifth graders. Data sources included validated questionnaires and an observation protocol of children’s behavior while interacting with AR books. The results of paired samples t-tests for children’s motivation indicated a statistically significant increase in attention (t (39) = - 3.07, p = 0.004), confidence (t (39) = - 2.44, p = 0.019) and satisfaction (t (39) = - 3.26, p = 0.002). Children read comfortably, seemed focused, and were eager to read more. They showed a high level of enthusiasm with AR technology when interacting with the first AR book, which notably decreased with the second book. The children maintained positive attitudes and behaviors towards AR. The study showed that even through short-term interactions, AR books have the potential to increase young students’ reading motivation. It adds to our knowledge concerning the use of AR books by primary school children, who are under-represented in the literature. Directions for future research are drawn.